The Abstraction of Reality in Cengiz Da?ci’s Benim Gibi Biri (Someone Like Me) - Üstün Kaya, Senem; Bilgin Topçu, Ümmühan (International Journal of Language and Literary Studies, 2022)
Cengiz Da?c? has been circling around certain facts since his first novels in the 50’s and in his many historically unique novels, he attempted to embrace his readers with human adventures, social and individual fractures based on the alienation and isolation of minorities from their own lands and perceivable periods in the shed of clashes and wars. This study aimed at interpreting the aspects of his style in his Benim Gibi Biri (Someone like Me) and presenting the differentiation of the work from its predecessors. The main purpose was to detect the concentration in the narration of Da?c?. The novel underscores the deviations in narration, cohesion and context in general when the character, Joseph becomes the voice of the conscience of the protagonist-narrator. Throughout spatial narration, we observed the traces of Cengiz Da?c? in a silhouette revealing his own personality and experience in actual life. The author’s psychology, outbursts, rebels, traumas and feelings are reflected through the main character, Joseph Tucknell. The deviations in narration highlights the scenes that create pathos for the readers when language becomes poetic. This study involves three main parts. In the first part, the novel Benim Gibi Biri (Someone like Me) by Cengiz Da?c? is analyzed in terms of characterization, themes and setting. Secondly, the focus was on the narrative techniques and cohesion within the context of the text. Finally, it was concluded that Cengiz Da?c? applied essential techniques to abstract his ideas from his fiction in this notable novel, distinguished from his previous works. Therefore, his works still mark the literary canon in terms of unique style and themes.